Gentrification and Resistance in Latin American Cities. The Example of Santiag o de Chile (Andamios, Revista de Investigación Social, 2013)
This paper discusses the modalities and possibilities to apply the term gentrification in the context of Latin-American cities. For this purpose, it is crucial to develop a critical exercise that dissociates the term from the traditional debates arising from the Anglophone world. As a result of this dialectical process, we propose its application in two dimensions for which it appears to have a particular relevance: the gentrification by real estate agents and the interrelation between gentrification and neighbourhood struggles. These are the two aspects we consider appropriate to reveal the hidden consequences of contemporary urban policies and to re-politicise urban studies from a perspective that is related to the demands of citizens. Such critical reflection leads us to a conceptual proposition that is latter exemplified by the case of Santiago, Chile, a paradigmatic city for the application of neoliberal urban policies causing gentrification.
Keywords: Gentrification; Critical Urban Theory; Real Estate Market; Resistance; Santiago de Chile